O estranhamente familiar na obra de Attilio Colnago - Miranda, Christine Ribeiro (2014)
This thesis investigates the unheimlich (uncanny), a concept on psychoanalysis developed by Freud, in works belonging to 4 (four) of the painter Attilio Colnago's series: "Dialogues with Passion" ("Diálogos com a Paixão"), “10+1 Dangerous Ways to Love” (“